PENINGKATAN KETERAMPILAN MENYIMAK DENGAN MENGGUNAKAN MEDIA AUDIO BAGI SISWA KELAS V SEKOLAH DASAR NEGERI - Nasution, Laila Ashuri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research base of fact in field that study of Indonesia language in Class V SDN 10 Sapiran, Teacher still predominate studies process and cannot entangle student participation directly. The condition result make lower result of learning study of Indonesia language as according to KKM which have been specified that is 70. Therefore not conducted by research with aim to increase result of learning Indonesia language by using Audio. That research use Approach qualitative and  quantitative, while this type research that is Research Action Class with this device research cover, (1) Planning, (2) Execution, (3) observation, and (4) Refleksi. Become can be concluded that study of Indonesia language by using Audio can improve result learn V class student 10 Sapiran Bukittinggi City. Kata Kunci: keterampilan menyimak; pembelajaran bahasa Indonesia; media audio.